Finite Difference Technique for reliable MHD steady flow through channels permeable boundaries - Kumar A.; Saket R.K.; Varshney C.L.; Maurya S.L. (My University, 2025)
This paper describes the combined wall slip and reliable MHD steady flow of the conducting viscous incompressible fluid through channels permeable boundaries. The governing equations have been solved by Finite Difference Technique. The analytical results and conclusions have been presented and discussed through various graphs. Results presented in this paper revealed that the fluid velocity can be replaced by a magnetic field and the wall slip. Appropriate result shows that the wall skin friction increases with suction and decreases with injection. Copyright © 2010 Inderscience Enterprises Ltd.